Interface Engineering of Needle‐Like P‐Doped MoS2/CoP Arrays as Highly Active and Durable Bifunctional Electrocatalyst for Overall Water Splitting. Issue 6 (9th February 2021) - Hu, Yan; Yu, Hongbo; Qi, Luoluo; Dong, Jiaxin; Yan, Puxuan; Taylor Isimjan, Tayirjan; Yang, Xiulin
Abstract: Developing a bifunctional water splitting catalyst with high efficiency and low cost are crucial in the electrolysis water industry. Here, we report a rational design and simple preparation method of MoS2 ‐based bifunctional electrocatalyst on carbon cloth (CC). The optimized P‐doped MoS2 @CoP/CC catalyst presents low overpotentials for the hydrogen (HER) and oxygen evolution reactions (OER) of 64 and 282 mV in alkaline solution as well as 72 mV HER overpotential in H2 SO4 at a current density of 10 mA cm −2 . Furthermore, P‐MoS2 @CoP/CC as a bifunctional catalyst delivered relatively low cell voltages of 1.83 and 1.97 V at high current densities of 500 and mA cm −2 in 30 % KOH. The two‐electrode system showed a remarkable stability for 30 h, even outperformed the benchmark RuO2 ||Pt/C catalyst. The excellent electrochemical performance can be credited to the unique microstructure, high surface area, and the synergy between metal species. This study presents a possible alternative for noble metal‐based catalysts to overcome the challenges of industrial applications. Abstract : Mastering the size : Needle‐like P‐doped MoS2 @CoP on carbon cloth is fabricated as a bifunctional electrocatalyst for large‐scale hydrogen generation from water.